Remnants - Irvin, Maurice J., author; Doenges, Judy, advisor; Becker, Leslee, committee member; Prince, Eric, committee member (Colorado State University. Libraries, 2015)
This thesis is a collection of six short stories written and revised between 2011 and 2015. I have presented them here in the order in which they were written chronologically. The titular story is included for the sake of completion. The title "Remnants" itself is an inside joke to the author and the author alone. It refers equally to the characters contained within these stories, the state of the stories themselves, as well as the state of the author. We are all tired, and frankly, sick of each other.